Komensalisme Budaya dalam Tradisi Cawir Metua di Tengah Keberagaman Etnis: Studi Kasus Masyarakat Karo di Kabanjahe - Erni Khairunisa; Windu Asmoro; Khay Ratu Nisa; Erni Khairunisa (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study examines the Cawir Metua tradition as a medium of cultural commensalism, which represents interethnic interaction that reflects tolerance, mutual respect, and social cohesion without the need for assimilation. Cawir Metua continues to exist as a symbol of Karo community identity and has also developed into a shared space for the multicultural community in Kabanjahe to maintain social harmony. The purposes of this study are: (1) to identify the funeral ritual process of Cawir Metua in Kabanjahe District, Karo Regency; (2) to analyze the existence of the Cawir Metua tradition among multicultural communities; and (3) to describe the opportunities and challenges in preserving the tradition in the era of globalization. This research employed a qualitative method with descriptive analysis techniques proposed by Miles and Huberman, including observation, interviews, and documentation. The participants consisted of: (1) the Karo ethnic community (as the main informant), (2–3) additional Karo informants, (4–5) Javanese informants, (6–7) Batak informants, and (8–9) Minangkabau informants. The findings reveal that the procession includes several stages: (1) family preparation and deliberation (rerembukan), (2) notification of grief to relatives (penjuluken beras), (3) implementation of traditional rituals, (4) presentation of ulos (final ulos), (5) coffin closing (turang), followed by (6) the burial and thanksgiving ceremony (ngembahken kiniteken). The existence of this tradition within a multicultural society demonstrates a dynamic of harmonious cultural interaction. However, its preservation faces significant challenges in the fast and practical era of globalization. Therefore, collaboration among local communities, the government, academics, and younger generations is essential to safeguard this cultural heritage in an adaptive yet authentic manner.